Solid Electrolytes for Advanced Applications Garnets and Competitors - Murugan, Ramaswamy; Weppner, Werner (Springer International Publishing : Imprint: Springer, 2019)
This book highlights the state of the art in solid electrolytes, with particular emphasis on lithium garnets, electrolyte-electrode interfaces and all-solid-state batteries based on lithium garnets. Written by an international group of renowned experts, the book addresses how garnet-type solid electrolytes are contributing to the development of safe high energy density Li batteries. Unlike the flammable organic liquid electrolyte used in existing rechargeable Li batteries, garnet-type solid electrolytes are intrinsically chemically stable in contact with metallic lithium and potential positive electrodes, while offering reasonable Li conductivity. The book's respective chapters cover a broad spectrum of topics related to solid electrolytes, including interfacial engineering to resolve the electrolyte-electrode interfaces, the latest developments in the processing of thin and ultrathin lithium garnet membranes, and fabrication strategies for the high-performance solid-state batteries. This highly informative and intriguing book will appeal to postgraduate students and researchers at academic and industrial laboratories with an interest in the advancement of high energy-density lithium metal batteries.